(untitled) (Indian Journal of Animal Production and Management, 2016)
The present study was conducted to investigate the effect of housing system on occurrence of diseases and time utilization pattern. Sixteen advanced pregnant Holstein Fresian cows were randomly divided equally into two groups of eight animals each (Group A as under conventional tie barn housing system and Group B as under loose housing system). Both the groups were reared under similar system of feeding and management except housing system. Most of the major parameters of occurrence of diseases showed non-significant differences between conventional and loose housing system. Time requirement for feeding and cleaning operation was significantly higher (P < 0.01) in conventional housing system (94.02 ± 1.4 and 92.49 ± 2.9 mins) than, that of loose housing system (61.49 ± 0.77 and 66.86 ± 0.65 mins) however, time requirement for milking operation was significantly higher (P < 0.01) in loose housing system (233.2 ± 4.19 mins) than, that of conventional housing system (209.12 ± 4.2 mins).Total time (minutes) utilization per day in conventional housing was significantly higher (P < 0.05) than, that of loose housing system. Rearing of cows under loose housing is beneficial over conventional housing system which gives better milk production without affecting health and minimum time utilization for feeding and cleaning operations except milking operation time than, that of conventional housing system. Moreover,the rearing of cattle under loose housing system was cost effective than, that of the conventional housing system.